Determinants Of Learning Motivation In Electronics-Based Industry - Luwe, Chin Kei (2002)
The purpose of this study was to identify some determinants that motivate learning among employees in manufacturing organisations. The study examines the mediating role played by employee's perceived job utility of training in linking the relationship of three independent variables and the dependent variable-learning motivation